Analisis Makna Cinta dan Keberanian dalam Lagu “Taruh” Nadin Amizah menggunakan Pendekatan Semiotika untuk Mengungkap Simbol Tersembunyi - Dwi Wulandari; Sri Dwi Fajarini (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study explores the meaning of love and courage in the lyrics of Nadin Amizah's song "Taruh". Music serves as a cultural medium that reflects the construction of social reality, and song lyrics often become a space for expressing personal and collective experiences. The song "Taruh" illustrates the emotional complexity present in human relationships, particularly in interpreting the feelings of love intertwined with acts of bravery. This research employs Ferdinand de Saussure's semiotic theory by examining the syntagmatic and paradigmatic relations within the song's lyrics. The descriptive qualitative method is applied, with data obtained through non-participant observation and literature study. The findings indicate that the lyrics of "Taruh" do not portray an idealized version of love; instead, they express a more realistic view of love as something that includes pain, vulnerability, and imperfection. Interestingly, within those imperfections, there is a profound sense of courage—a willingness to endure, to remain, and to accept wounds as a part of emotional life. The syntagmatic analysis highlights how the arrangement of words in each stanza reflects stages of emotional struggle, longing, acceptance, and resilience. On the other hand, the paradigmatic analysis reveals that while alternative words could have been chosen, the selected diction intensifies the emotional nuance without shifting the central message of the narrative. Overall, the song constructs a layered narrative of love, where courage is found not in grand gestures but in silent endurance. This study shows how popular music, through its poetic structure, can communicate complex emotional truths and contribute to deeper cultural understandings of human emotion.